How Universities Gaslight EDI&I Initiatives: Mapping Institutional Resistance to Structural Change - MacKenzie, Megan; Sensoy, Özlem; Johnson, Genevieve Fuji; Sinclair, Nathalie; Weldon, Laurel (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2023)
Despite the visibility of equity, diversity, inclusion, and Indigenization (EDI&I) discourses within large institutions, such as post-secondary institutions, research has chronicled only modest advancements on these stated values. Blocks to advancements in EDI&I stem, in part, from the structural nature of racist and sexist domination, and especially its embeddedness in both formal and informal norms of institutions. Based on a close examination of two EDI&I initiatives in university contexts, and direct experiences of “pushback” against these initiatives, this article conceptualizes institutional gaslighting, whereby universities paradoxically both embrace EDI&I discourse, on the one hand, while simultaneously deploying strategies that prevent dismantling systemic inequalities, on the other. A conceptualization of this dynamic is designed to help others identify and address forms of resistance, especially in settings of high stated value, and ultimately advance these values within large institutions.